2018
DOI: 10.1002/jca.21647
|View full text |Cite
|
Sign up to set email alerts
|

Indication‐specific immunomodulatory effects of extracorporeal photopheresis: A pilot study in heart transplanted patients

Abstract: In our pilot study, we showed different stimulatory effects of ECP on pDCs and cytokines among prophylactic and therapeutic ECP therapy after HTx. Immunological monitoring should be included in a larger clinical study of ECP treatment following HTx and to identify predictable parameters for ECP efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…2,6 In general, therapy of DSA-MR involves a combination of steroids, plasmapheresis, extracorporeal photopheresis, anti-T-lymphocyte IgG, and intravenous immunoglobulin (IVIG) applications. 4,6,7 While common therapeutic IVIG consist of IgG only, novel intravenous IgM-enriched immunoglobulin (IGM-IVIG) consist of a combination of 76% IgG, 12% IgM, and 12% IgA and can address DSA-MR by scavenging activated complement, neutralization of DSA, inhibition of the activation of cytotoxicity effector cells, inhibition of tissue migration granulocytes and monocytes, and activation of regulatory T cells. [8][9][10][11][12] IGM-IVIG are by now regularly used in the therapy of severe sepsis and showed first promising results in the therapy of DSA-MR in lung and heart transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…2,6 In general, therapy of DSA-MR involves a combination of steroids, plasmapheresis, extracorporeal photopheresis, anti-T-lymphocyte IgG, and intravenous immunoglobulin (IVIG) applications. 4,6,7 While common therapeutic IVIG consist of IgG only, novel intravenous IgM-enriched immunoglobulin (IGM-IVIG) consist of a combination of 76% IgG, 12% IgM, and 12% IgA and can address DSA-MR by scavenging activated complement, neutralization of DSA, inhibition of the activation of cytotoxicity effector cells, inhibition of tissue migration granulocytes and monocytes, and activation of regulatory T cells. [8][9][10][11][12] IGM-IVIG are by now regularly used in the therapy of severe sepsis and showed first promising results in the therapy of DSA-MR in lung and heart transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…One hypothesizes that the return of apoptotic T cells activates dendritic cells (DCs), which leads to cytokine alterations and results in an increase in regulatory T cells (T regs ) (6). The other hypothesizes that ECP presents an apoptotic stimulus that affects activated alloreactive T cells, which are preferentially processed and presented by DCs resulting in suppression of alloantigenresponding T cells (3). In particular, the effect of ECP on an increase of T regs in HTx was studied by different research groups (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…For example, questions remain about the best time point to initiate or reintroduce ECP therapy as well as about the optimal number of ECP treatments that are required for different indications, such as ACR or antibody-mediated rejection (AMR). Thus, a reliable monitoring tool for optimizing ECP therapy is required ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring of regulatory T cells frequencies during ECP treatment has been performed in several trials. Some reports describe an increase in circulating Treg percentages over the course of several months during ECP treatment, predominantly in the context of GVHD; however, stable or decreasing Treg frequencies were reported in other pathologic contexts . In most cases, Treg numbers display large inter‐individual heterogeneity and do not necessarily correlate with clinical responses .…”
Section: Introductionmentioning
confidence: 99%
“…Some reports describe an increase in circulating Treg percentages over the course of several months during ECP treatment, [11][12][13][14] predominantly in the context of GVHD; however, stable or decreasing Treg frequencies were reported in other pathologic contexts. 13,15 In most cases, Treg numbers display large inter-individual heterogeneity 16 and do not necessarily correlate with clinical responses. 17 In the context of CTCL treatment, it has been suggested that ECP could induce a cytotoxic response directed toward the malignant clone.…”
Section: Introductionmentioning
confidence: 99%